Optimization of Anther Cultur for Pepper (Piper nigrum L.) as an Initial Stage in the Biotechnology Process of Superior Seedling Propagation - Tika Rahma Yunita; Muliani Muliani; Zaenal Mutaqin (Protech Biosystems Journal, 2025)
One of breeding activities aimed at increasing the genetic diversity of pepper plants is through anther culture. This study aims to evaluate combination of MS media supplemented with hormones for callus formation from pepper anther explants. The method used was a factorial Completely Randomized Design (CRD), with the first factor being three media compositions: full-strength MS, ½ MS, and ¼ MS; and the second factor being five combinations of hormone, namely: A. 0 ppm NAA : 1 ppm BAP; B. 1 ppm NAA : 0 ppm BAP; C. 1 ppm NAA : 1 ppm BAP; D. 2 ppm NAA : 1 ppm BAP; and E. 1 ppm NAA : 2 ppm BAP. The results of this research are a significant contribution to the development of tissue culture-based bioprocess system for producing superior pepper seedling through anther culture technology. The application of ¼ MS medium supplemented with 2 ppm NAA and 1 ppm BAP induced callus formation at a rate of 10%.